2017
DOI: 10.1371/journal.pntd.0005702
|View full text |Cite
|
Sign up to set email alerts
|

Persistent infection due to a small-colony variant of Burkholderia pseudomallei leads to PD-1 upregulation on circulating immune cells and mononuclear infiltration in viscera of experimental BALB/c mice

Abstract: BackgroundMelioidosis is a neglected tropical disease endemic across South East Asia and Northern Australia. The etiological agent, Burkholderia pseudomallei (B.pseudomallei), is a Gram-negative, rod-shaped, motile bacterium residing in the soil and muddy water across endemic regions of the tropical world. The bacterium is known to cause persistent infections by remaining latent within host cells for prolonged duration. Reactivation of the recrudescent disease often occurs in elders whose immunity wanes. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…In an acute infection, such an inhibitory signal would limit the number of effector T cells during T cell expansion [ 30 ], whereas during chronic infection, due to persistent exposure to antigens, this interaction renders the T cells unresponsive, leading to T cell exhaustion [ 31 ]. Increasing evidence suggests that PD-1 has a role in the inhibition of effector T cell responses in persistent Mycobacterium tuberculosis [ 32 ] and persistent viral infections [ 33–35 ], which we demonstrated in a murine model of persistent B. pseudomallei infection [ 36 ]. Upregulation of PD-L1 on polymorphonuclear neutrophils (PMNs) of melioidosis patients has been shown to impair T cell functions [ 37 ].…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…In an acute infection, such an inhibitory signal would limit the number of effector T cells during T cell expansion [ 30 ], whereas during chronic infection, due to persistent exposure to antigens, this interaction renders the T cells unresponsive, leading to T cell exhaustion [ 31 ]. Increasing evidence suggests that PD-1 has a role in the inhibition of effector T cell responses in persistent Mycobacterium tuberculosis [ 32 ] and persistent viral infections [ 33–35 ], which we demonstrated in a murine model of persistent B. pseudomallei infection [ 36 ]. Upregulation of PD-L1 on polymorphonuclear neutrophils (PMNs) of melioidosis patients has been shown to impair T cell functions [ 37 ].…”
Section: Introductionmentioning
confidence: 63%
“…PD-1 was recently shown to be upregulated in persistent B. pseudomallei infections in mice [ 36 ], which nonetheless has not been proven in humans. Here, healthy PBMCs were exposed to B. pseudomallei and B. thailandensis antigens in vitro and, following 18 h of incubation, cells were assessed for PD-1 and TIM-3 expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three different strains of B. pseudomallei used were OB, OS and K9. OS is a small colony variant (SCV) which is associated with persistent infection and antibiotic resistance whereas OB is its wild-type (See et al, 2017). K9 was isolated from a melioidosis patient and had been widely used in experimental B. pseudomallei.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, using a mice model, See et al. (2017) ( 115 ) characterized the regulation of PD-1 and CTLA-4 levels on B cells, NK cells, and monocytes and confirmed that persistent infection with B. pseudomallei small colony variants (SVCs) can concomitantly cause PD-1 upregulation on B cells, NK cells and monocytes signifying host immune exhaustion. The SCVs were found to up-regulate the PD-1 on NK cells and monocytes in contrast to its WT counterpart.…”
Section: Cell-mediated Immunity and B Pseudomalleimentioning
confidence: 98%